2020
DOI: 10.1111/nhs.12775
|View full text |Cite
|
Sign up to set email alerts
|

Health beliefs and practices regarding cervical cancer screening among women in Nepal: A descriptive cross‐sectional study

Abstract: The health beliefs and practices regarding cervical cancer screening among women in the mountainous and Terai region of Nepal were investigated and examined for the differences. A descriptive cross-sectional study was conducted with a purposive sample of 216 in mountainous and 294 in Terai. The interview tools were a sociodemographic scale, a Nepalese Health Belief Model Scale for Cervical Cancer followed by the Screening Test. Chi-square test, binary logistic regression, Mann-Whitney U, and Kruskal-Wallis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 27 publications
(46 reference statements)
0
13
1
Order By: Relevance
“…Compared to other studies using Guvenc’s scale, our results suggest that hard-to-reach women from Bogotá have lower perceived susceptibility [ 22 , 37 – 40 ], higher perceived severity [ 21 , 22 , 37 – 42 ], higher perceived benefits [ 38 – 44 ] and lower perceived barriers [ 21 , 38 , 41 , 42 , 45 , 46 ], towards cervical cancer screening. Recent reviews concluded that these beliefs have been less researched in Latin America [ 47 , 48 ].…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Compared to other studies using Guvenc’s scale, our results suggest that hard-to-reach women from Bogotá have lower perceived susceptibility [ 22 , 37 – 40 ], higher perceived severity [ 21 , 22 , 37 – 42 ], higher perceived benefits [ 38 – 44 ] and lower perceived barriers [ 21 , 38 , 41 , 42 , 45 , 46 ], towards cervical cancer screening. Recent reviews concluded that these beliefs have been less researched in Latin America [ 47 , 48 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Similarly, perceived susceptibility was associated with higher uptake rates in Ghana [ 55 ], Ethiopia [ 39 ] and Iran [ 56 ]. Additionally, higher perceived benefits were found to encourage screening behaviours in Nepal [ 41 ], Ghana [ 55 ] and Ethiopia [ 57 ]. In a recent review, Simbar et al [ 58 ] concluded that training-based interventions are able to modify perceived susceptibility and benefits, leading to behavioural changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pap smear test was reported to be the cervical cancer screening method in 15 studies; 3,4,18,26,31e42 of these, three studies reported both VIA and Pap smear test as screening methods. 33,40,42 None of the 17 included studies reported the use of liquid-based cytology or screening by HPV test (see Table 2).…”
Section: Cervical Cancer Screening Methodsmentioning
confidence: 99%
“…3,18,39,41,42 We compared screening utilization in rural and urban areas among the community-based studies: cervical cancer screening utilization using the Pap smear test ranged from 3.3% (21e65 years) to 14.8% (20e65 years) in rural areas, and 7.3% (21e65 years) to 20.1% (20e65 years) in the urban areas (Table 1). 18,40…”
Section: Study Selectionmentioning
confidence: 99%